Haris Moejahid Pencetus Medical Hacking sebagai Pengobatan tanpa Obat dan Operasi - Pribadi, Syofiah; Achmad Hidayat, Acep; Thohir, Ajid; Samidah, Ida; Nursalim, Danni (Bulletin of Community Engagement, 2024)
Medical Hacking represents a groundbreaking Islamic medical paradigm aimed at enabling individuals to attain wellness without reliance on pharmaceuticals or surgical interventions, boasting a remarkable success rate of 95%. Central to Medical Hacking is the empowerment of individuals to administer self-care within their homes. Haris Moejahid, a pioneering figure in the Islamic health movement and renowned as a medical hacker, has championed a therapeutic approach rooted in manual techniques, facilitating holistic healing and spontaneous recovery under divine sanction. This article delves into the transformative journey of Haris Moejahid, illuminating his enduring influence and legacy in the realm of medical hacking therapy. In the aftermath of Haris Moejahid's passing, his teachings continue to inform and inspire practitioners, laying the groundwork for the evolution of non-invasive, pharmaceutical-free therapies. The narrative examines facets of Haris Moejahid's hagiography, shedding light on initiatives by his followers to propagate Medical Hacking, encompassing foundational concepts, methodologies, and seminal works in the field. This research contributes to a deeper understanding of the relationship between faith and scientific knowledge in maintaining health. Through various methods such as leech therapy, honey therapy, cupping, and other methods, Haris Moejahid has made a sustained contribution to improving public health. Keywords: Medical Hacking, Health Without Drugs and Surgery, Haris Moejahid